1998
DOI: 10.1021/ma9800966
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Imidization Study by Spectroscopic Techniques. 2. Polyamic Acids

Abstract: Chemical imidization of polyamic acid based on 1,5-diaminonaphthalene and a dianhydride was studied by UV−visible and FT-IR ATR techniques under various reaction conditions, such as polyamic acid concentration, solvent condition (dry vs humidity-exposed NMP), catalysts of tertiary amines with different degrees of steric crowding and base strength, and the concentration of the acetic anhydride and pyridine. With acetic anhydride and pyridine, the reaction was very similar to that of the model amic acids, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…It is also observed that, despite its relatively high basicity, TEA does not promote imidization to any significant extent. A similar observation was reported by Kailani et al 25 for TEA-catalyzed imidization of a polyamic acid in N-methylpyrollidone solution. In contrast to the undegraded PAA ( Figure 5B), the MALDI spectrum for degraded PAA ( Figure 5A) clearly proves the identity of the poly(pyromellitic dianhydride-co-4,4′-oxydianiline) amic acid.…”
Section: B Maldi Analysis Of 2-fluoro-1-methylpyridinium (Fmp) Derivsupporting
confidence: 88%
“…It is also observed that, despite its relatively high basicity, TEA does not promote imidization to any significant extent. A similar observation was reported by Kailani et al 25 for TEA-catalyzed imidization of a polyamic acid in N-methylpyrollidone solution. In contrast to the undegraded PAA ( Figure 5B), the MALDI spectrum for degraded PAA ( Figure 5A) clearly proves the identity of the poly(pyromellitic dianhydride-co-4,4′-oxydianiline) amic acid.…”
Section: B Maldi Analysis Of 2-fluoro-1-methylpyridinium (Fmp) Derivsupporting
confidence: 88%
“…32 In another report, E a for chemical imidization of a poly(amic acid) of 4,4 0 -(hexafluoroisopropylidene)diphthalic anhydride and 1,5-diaminonaphthalene was presented to be 12.3 kJ/mol when an approximately 13:1 molar ratio of amine catalyst to PAA repeating unit was used. 28 …”
Section: Determination Of Activation Energy Of Chemical Imidizationmentioning
confidence: 99%
“…There have been a few reports on low-temperature imidization, but they have mainly focused on the imidization kinetics of fully aromatic poly(amic acid)s. 27,28 In the present work, we prepared transparent polyimide films from partially aliphatic poly(amic acid)s by means of low-temperature imidization and also studied the imidization kinetics.…”
mentioning
confidence: 99%
“…Tertiary alkylamines are generally used as Brønsted bases in organic synthesis 1–2. On the other hand, many reactions are known, where tertiary amines act as nucleophilic catalysts 3–32. 1,4‐Diazabicyclo[2.2.2]octane (DABCO, 1e ) and quinuclidine ( 1f ), for example, are common catalysts in Baylis–Hillman reactions7 and in cyclopropanations of Michael acceptors 8 .…”
Section: Introductionmentioning
confidence: 99%